Tracking anadromous fish over successive freshwater migrations reveals the influence of tagging effect, previous success, and abiotic factors on upstream passage over barriers - Davies, Peter; Robert Britton, J.; Castro-Santos, Theodore; Crundwell, Charles; Dodd, Jamie R.; Nunn, Andrew D.; Velterop, Randolph; Bolland, Jonathan D. (Canadian Journal of Fisheries and Aquatic Sciences, 2023)
Predicting and mitigating the impact of anthropogenic barriers on migratory fish requires an understanding of the individual and environmental factors that influence barrier passage. Here, the upstream spawning migrations of iteroparous twaite shad Alosa fallax were investigated over three successive spawning migrations in a highly fragmented river basin using passive acoustic telemetry (n = 184). More fish approached and passed barriers in the lower river reaches than further upstream, with the median cumulative weir passage time of 4.6 (1.8–9.2) days representing 18% of their time in the river. Returning fish in their second year had significantly higher weir passage rates than in their tagging year, with passage rates also positively influenced by previous passage success. Higher water temperatures and river levels also had positive impacts on passage rates. Lower weir passage rates by newly tagged individuals suggest that reliance on within-year passage estimates in telemetry-based barrier impact assessments could result in conservative results, while the higher passage rates of previously successful versus unsuccessful individuals suggest a conserved motivation and/or inherent ability to pass barriers.
Keywords: Telemetry; Migration; Dams; Fishes; Anadromous species